Grammatical Errors In English Speaking Material In Junior High School - Rakyan Thariq Fahd Muhammad (CV. Ulil Albab Corp, 2026)
The purpose of this article is to examine the perception of junior high school students towards errors in learning English in terms of speaking, this study aims to identify the types of errors that are often found in the realm of junior high school students and to determine the impact on students' learning experiences. Using qualitative methods, data were collected by interviewing students and teachers and field surveys. The results of several interviews and surveys showed various subjects that were problems in learning English speaking, namely subject-verb conformity, use of time (tenses), and word order. Because some of these problems cause confusion and also difficulties for students in self-confidence in speaking English. This study emphasizes the importance of teaching methods that are in accordance with children's learning styles to increase effectiveness in learning. This study contributes to supporting the development of learning and also students' learning styles.